2016
DOI: 10.1371/journal.pone.0149628
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of FGFR1 Locus in sqNSCLC Reveals a Broad and Heterogeneous Amplicon

Abstract: FGFR1 amplification occurs in ~20% of sqNSCLC and trials with FGFR inhibitors have selected FGFR1 amplified patients by FISH. Lung cancer cell lines were profiled for sensitivity to AZD4547, a potent, selective inhibitor of FGFRs 1–3. Sensitivity to FGFR inhibition was associated with but not wholly predicted by increased FGFR1 gene copy number. Additional biomarker assays evaluating expression of FGFRs and correlation between amplification and expression in clinical tissues are therefore warranted. We validat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 27 publications
2
36
0
Order By: Relevance
“…In order to investigate whether the induction of oxidative stress by FGF/FGFR inhibition is a mechanism specific for FGF-dependent lung cancers, we tested the effect of NSC12 on two other human lung cancer cell lines: FGF-dependent H520 cells and FGF-independent HCC827 cells. H520 cells, like H1581 cells, are characterized by FGFR1 amplification and autocrine FGF stimulation ( Table S1 ) [ 19 ], whereas HCC827 cells are adenocarcinoma cells that harbor a tumor driving mutation in the TK domain of EGFR which makes these cells independent from the FGF/FGFR system, notwithstanding their FGF/FGFR expression ( Table S1 ) [ 25 ]. As previously reported [ 21 ], NSC12 significantly reduced the proliferation of FGF-dependent H520 cells, but not of FGF-independent HCC827 cells ( Figure 3 A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to investigate whether the induction of oxidative stress by FGF/FGFR inhibition is a mechanism specific for FGF-dependent lung cancers, we tested the effect of NSC12 on two other human lung cancer cell lines: FGF-dependent H520 cells and FGF-independent HCC827 cells. H520 cells, like H1581 cells, are characterized by FGFR1 amplification and autocrine FGF stimulation ( Table S1 ) [ 19 ], whereas HCC827 cells are adenocarcinoma cells that harbor a tumor driving mutation in the TK domain of EGFR which makes these cells independent from the FGF/FGFR system, notwithstanding their FGF/FGFR expression ( Table S1 ) [ 25 ]. As previously reported [ 21 ], NSC12 significantly reduced the proliferation of FGF-dependent H520 cells, but not of FGF-independent HCC827 cells ( Figure 3 A).…”
Section: Resultsmentioning
confidence: 99%
“…This promotes cancer cell survival, chemotherapy resistance and growth of lung tumor cell lines [ 14 , 17 ]. Accordingly, lung cancer cell lines (like NCI-H1581 and NCI-H520 cells) have been identified that harbor amplification of FGFR1 and are highly sensitive to FGFR inhibitors in vitro and in vivo [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Gene amplification Amplification of FGFR is reported to be present in 66% of cancers with an FGFRs alteration, with FGFR1 amplification being the most common (42%) (Helsten et al, 2015). Approximately 20% of the squamous cell carcinomas (SCC) of the lung present with FGFR1 amplification and this has been shown to be associated with smoking in a dose-dependent fashion (Rooney et al, 2016). Recently a meta-analysis showed that patients with FGFR gene amplification have a worse prognosis than FGFR wild-type patients.…”
Section: Fgfr In Cancermentioning
confidence: 99%
“…Fibroblast growth factor receptor 1 (FGFR1) is an emerging molecular target for the treatment of SCC of the lung [9][10][11], and several clinical trials of FGFR inhibitors in NSCLC are currently underway [12][13][14]. Amplification of the FGFR gene has been found in epithelial malignancies, such as gastric, breast, oral squamous cell, ovarian, and bladder carcinomas [15,16], and more recently, in lung SCC.…”
Section: Introductionmentioning
confidence: 99%